A COMPARISON OF THE CO-TREATMENT OF URBAN WASTEWATER AND ACIDIC WATER USING A TERNARY EMERGY DIAGRAM - BRAVO TOLEDO, LUIGI (2024)
THE PASCO REGION IN PERU IS AN AREA THAT HAS HISTORICALLY BEEN POLLUTED BY MINING ACTIVITY AND POPULATION GROWTH. AS A RESULT, THERE IS AN INCREASED PRODUCTION OF URBAN WASTEWATER AND ACIDIC WATER THAT CONTAMINATE LOCAL LAKES SUCH AS QUIULACOCHA AND PATARCOCHA. THE CONSTRUCTION OF A TREATMENT PLANT THAT CAN TREAT THE DIFFERENT TYPES OF WASTEWATERS HAS NOT YET BEEN STUDIED, AND ITS SUSTAINABILITY HAS NOT YET BEEN EVALUATED. THE OBJECTIVE OF THIS RESEARCH WAS TO PREDICT THE SUSTAINABILITY OF CO-TREATMENT SYSTEMS IN DIFFERENT SCENARIOS BETWEEN URBAN WASTEWATER AND ACIDIC WATER, EXPRESSED IN TERMS OF A TERNARY EMERGY DIAGRAM. THE DESIGN OF THE CO-TREATMENT PLANT WAS CARRIED OUT AT AN INFLOW OF 10 L/S. THE FIRST SCENARIO (TREATMENT I) HAS A PRIMARY SETTLER FOR THE MIXTURE OF URBAN WASTEWATER AND ACIDIC WATER, WHILE THE SECOND SCENARIO (TREATMENT II) INVOLVES A SETTLER AND A SUBSURFACE ARTIFICIAL WETLAND, AND THE THIRD SCENARIO (TREATMENT IIIA AND IIB) PRESENTS A SETTLER, AN ELECTROCOAGULATION SYSTEM AND A SECONDARY SETTLER; THIS SCENARIO DIFFERENTIATES BETWEEN THE USE OF URBAN WASTEWATER AND EUTROPHICATED WATER FROM PATARCOCHA LAKE. THE RESULTS OF THE TERNARY DIAGRAM SHOW THE CONTRIBUTIONS OF THE FRACTIONS OF RENEWABLE RESOURCES FROM TREATMENT I (69%), FROM TREATMENT II (65.7%), FROM TREATMENT IIIA (61.6%), AND FROM TREATMENT IIIB (21.8%); THE FRACTIONS OF NON-RENEWABLE RESOURCES IN TREATMENT I (26.13%), TREATMENT II (24.13%), TREATMENT IIIA (23.33%), AND TREATMENT IIIB (9.50%); AND THE FRACTIONS OF IMPORTED INPUTS IN TREATMENT I (4.84%), TREATMENT II (9.37%), TREATMENT IIIA (15.04%), AND TREATMENT IIIB (68.72%). IT IS CONCLUDED THAT THE USE OF A CO-TREATMENT SYSTEM FOR URBAN WASTEWATER AND ACIDIC WATER IS SUSTAINABLE IN THE LONG TERM WHEN USING AN ELECTROCOAGULATOR OR AN ARTIFICIAL WETLAND. © 2024 BY THE AUTHORS.